THE ROLE OF INFORMATION TECHNOLOGY (IT) IN RURAL DEVELOPMENT - Mukherjee, P.K. (SCHOOL SCIENCE, 2011)
There is no gainsaying the fact that the development and progress of all the constituents of a nation are necessary for its overall development. Almost 75 per cent of the population of our country lives in villages. The development of rural areas is, therefore, a must for the overall development of the country. Even in the present century, people in many rural areas are forced to live in conditions of extreme poverty. Governed by superstitions, they are an ignorant, a lot living under utter inhuman conditions confronted with total lack of medical and other infrastructural facilities. Therefore, besides meeting the fundamental needs of water, food, education, medical facility of the rural people, the socio-economic development of villages is also necessary. Certainly, it can play an important role in fulfilling this task.